Comparison of the Effect of Administration Time of Prophylactic Antibiotics on Post-Operative Wound Infection after Caesarean Section - Maryam Mushtaq, Humaira Rizwan, Shermeen Kousar, Ayesha Akram, Samina Irshad, Nasim Irshad, (Journal of Rawalpindi Medical College, 2021)
Objective: To compare the post-operative wound infection rate after cesarean section in women receiving prophylactic antibiotics before skin incision with women receiving antibiotic after cord clamping of baby. Study design: Randomized controlled trial Place and Duration of Study: Department of Obstetrics and Gynecology, Holy Family hospital, Rawalpindi from October 2017 to April 2018. Materials & Methods: 356 patients pregnant female of age 20-45 years who were at term undergoing elective cesarean section for any indication were enrolled. All the patients were randomly divided into two groups. Group A (study group) was comprised of patients who received prophylactic antibiotic dose 15-60 min before the start of surgery. Group B (control group) was comprised of patients who received the antibiotic after the cord clamping of the baby. The wound infection was noted for both the groups. All the patients were followed up for 8 days to assess infection. Data was analyzed using SPSS version 22. Results: Mean maternal age of the total study population found to be 28.6±5.3 years. Mean gestational age in all the enrolled patients found to be 37.7±1.2 weeks. Wound infection was noted in 28.4% (n=101) of total study population. Out of 101 total patients who presented with wound infection, 63 patients (62.4%) were of control group while only 38 (37.6%) patients belonged to study group. The difference was statistically significant (P<0.05). Conclusions: Prophylactic antibiotic are useful for controlling post cesarean wound infection. KEY WORDS: Cesarean delivery, Ceftriaxone, Wound infection